2001
DOI: 10.1093/ps/80.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of 13,14-dihydro-15-keto PGF2α and Progesterone During the Oviposition Cycle of the Domestic Goose (Anser anser domesticus)

Abstract: Plasma 13,14-dihydro-15-keto prostaglandin F2alpha (PGFM) and progesterone levels were determined in actively ovulating, 1- to 2-yr-old female geese (Anser anser domesticus) at hourly intervals during the oviposition cycle, using the enzyme immunoassay (EIA) technique. The plasma PGFM concentration showed a peak at the time of oviposition and decreased to a basal level after oviposition. Progesterone levels began to surge approximately 12 to 13 h before ovulation and reached a peak 2 to 3 h before ovulation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 23 publications
5
8
1
Order By: Relevance
“…This is somewhat different from European graylag geese ( Anser anser ) reported by Çelebi and Güven [12], which lay eggs mostly during the early part of the day. Oviposition is thought to be regulated by an interaction of endogenous rhythms with daily photoperiod [6], which determines neuroendocrine regulation of ovulation.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…This is somewhat different from European graylag geese ( Anser anser ) reported by Çelebi and Güven [12], which lay eggs mostly during the early part of the day. Oviposition is thought to be regulated by an interaction of endogenous rhythms with daily photoperiod [6], which determines neuroendocrine regulation of ovulation.…”
Section: Discussioncontrasting
confidence: 84%
“…Discovery of these genes is also important for molecule-aided selection of egg-laying performance [9]. The endocrine mechanisms that regulate the egg-laying cycle has been documented for the chickens [6,10,11], in which egg laying and ovarian follice recruitment are almost continuous, and so have the secretion patterns of progesterone and pgFM for graylag goose ( Anser anser ) [12]. However, for the Magang geese ( Anser cygnoid ) in which not only egg laying rate is low, but also the clutch or sequence egg size is limited to no more than the number of large yellow follicles (LYF) available before the first egg in a sequence, resulting extended interruption of over 20 days between the egg clutches [2].…”
Section: Introductionmentioning
confidence: 99%
“…These values were higher than those found by Stasko et al [30], who obtained values close to 36 h, using the same definition of a clutch as in the present paper. The present estimates were close to the duration between successive ovipositions obtained by Chun Xiang and He Guang [7] in the White Roman geese (45.7 h), and lower than the duration of 46 to 48 h observed by Celebi and Guven [6]. Thus, a variation can be found between breeds and between management systems for an interval between ovipositions.…”
Section: Detailed Analysis Of the Laying Rhythmsupporting
confidence: 83%
“…1); all geese showed a proportion of eggs separated by two days (around 50%) higher than the proportion of eggs separated by one day (around 30%). Recent data on plasma progesterone in geese showed a single pre-ovulatory peak within an interval of 46 to 48 h separating two ovipositions, the peak took place 12 to 13 h before ovulation [6] which suggested that hormonal secretions did not follow a 24 hours rhythm. Furthermore, the duration of egg formation was estimated to vary from 42 to 44 h in white Roman geese [7], which does not match easily with a 24 hour rhythm of egg laying.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation